The Home Bias in Equities and Distribution Costs2. (5th March 2015) - Harms, Philipp; Hoffmann, Mathias; Ortseifer, Christina
Abstract We show that incorporating distribution costs into a general equilibrium model of international portfolio choice helps to explain the home bias in international equity investment. Our model is able to replicate observed investment positions for a wide range of parameter values, even if agents have an incentive to hedge labor income risk by purchasing foreign equity. This is because the existence of a retail sector affects both the correlation of domestic returns with the domestic price level and the correlation between financial and non‐financial income.